Azelnidipine plus olmesartan versus amlodipine plus olmesartan on arterial stiffness and cardiac function in hypertensive patients: a randomized trial - Takami T; Saito Y (Dove Medical Press, 2013)
CorrigendumTakami T, Saito Y. Drug Design, Development and Therapy. 2013;7:175–183. On page 177, line 26, heading "Measurement of LVMI and LF diastolic function" should have been "Measurement of LVMI and LV diastolic function". Line 32, "Devereux et al18" should read "Devereux et al19". Line 40, "(E/e’ ratio) were measured as previously described.19" should read "(E/e’ ratio) were measured as previously described.20". On page 181, line 15, "baPWV with LVMI.20" should read "baPWV with LVMI.21". Line 23, "baPWV and LVMI, E/A ratio.20" should read "baPWV and LVMI, E/A ratio.21,22". Line 28 "diastolic dysfunction.21" should read "diastolic dysfunction.23". Line 38 "is high.22" should read "is high.24". Line 39, "in clinical treatment.23" should read "in clinical treatment.25". Line 57, "A recent cohort study24" should read "A recent cohort study21".On page 182, line 1, "diastolic heart failure.25" should read "diastolic heart failure.26". Line 3, "untreated hypertensive patients.26" should read "untreated hypertensive patients.27". Line 6, "linear regression analysis.27" should read "linear regression analysis.21".On page 183, the references 18 to 27 should be updated as shown below:18. Takami T. Evaluation of arterial stiffness in morning hypertension under high-dose valsartan compared to valsartan plus low-dose diuretic. Hypertens Res. 2009;32:1086–1090.19. Devereux RB, Palmieri V, Sharpe N, et al. Effects of once-daily angiotensin-converting enzyme inhibition and calcium channel blockade-based antihypertensive treatment regimens on left ventricular hypertrophy and diastolic filling in hypertension: the prospective randomized enalapril study evaluating regression of ventricular enlargement (PRESERVE) trial. Circulation. 2001;104:1248–1254.20. Ito H, Ishii K, Kihara H, et al. Adding thiazide to a renin-angiotensin blocker improves left ventricular relaxation and improves heart failure in patients with hypertension. Hypertens Res. 2012;35:93–99.21. Xu L, Jiang CQ, Lam TH, et al. Arterial stiffness and left-ventricular diastolic dysfunction: Guangzhou Biobank Cohort Study-CVD. J Hum Hypertens. 2011;25:152–158.22. Kim MN, Park SM, Shim WJ, et al. The relationship between aortic stiffness and left ventricular dyssynchrony in hypertensive patients with preserved left ventricular systolic function. Clin Exp Hypertens. 2012;34:410–416.23. Schillaci G, Pasqualini L, Verdecchia P, et al. Prognostic significance of left ventricular diastolic dysfunction in essential hypertension. J Am Coll Cardiol. 2002;39:2005–2011.24. Ommen SR, Nishimura RA, Appleton CP, et al. Clinical utility of Doppler echocardiography and tissue Doppler imaging in the estimation of left ventricular filling pressures: A comparative simultaneous Doppler-catheterization study. Circulation. 2000;102:1788–1794.25. Hillis GS, Møller JE, Pellikka PA, et al. Noninvasive estimation of left ventricular filling pressure by e/e′ is a powerful predictor of survival after acute myocardial infarction. J Am Coll Cardiol. 2004;43:360–367.26. Yambe M, Tomiyama H, Hirayama Y, et al. Arterial stiffening as a possible risk factor for both atherosclerosis and diastolic heart failure. Hypertens Res. 2004;27:625–631.27. Jaroch J, Łboz Grudzień K, Bociąga Z, et al. The relationship of carotid arterial stiffness to left ventricular diastolic dysfunction in untreated hypertension. Kardiol Pol. 2012;70:223–231.Read the original article